Porphyria cutanea tarda: An uncommon condition in a patient on chronic hemodialysis - Yedabettu Janardhana Anupama; Yabagodu Ramavakoda Parameshwara (Wolters Kluwer Medknow Publications, 2023)
Patients with chronic kidney disease can have many dermatological manifestations. One of the very rare conditions is porphyria cutanea tarda (PCT), which manifests with hyperpigmentation of skin and photosensitivity along with painful bullae in sun-exposed areas. It is due to deficiency of uroporphyrinogen III decarboxylase enzyme which takes part in heme synthesis. The deficiency could be genetic or sporadic. Iron therapy and hepatitis C infection are known to precipitate these lesions. We report a case of PCT in a woman undergoing chronic maintenance hemodialysis, review the literature, and discuss the problems with management specific to the dialysis population.